Lack of confirmatory data following Article 12 MRL reviews for 2,4‐d, fenhexamid and iprovalicarb - European Food Safety Authority (EFSA) (Wiley, 2021)
Abstract The European Commission mandated EFSA to issue a statement concerning confirmatory data that were not submitted by the set deadline by the applicant following Article 12 reviews under Regulation (EC) No 396/2005 for the following substances/commodity combination: 2,4‐d on buckwheat and other pseudo‐cereals, fenhexamid on kiwis, iprovalicarb on lettuces, escaroles/broad‐leaved endives and roman rocket/rucola. EFSA prepared a statement containing a final conclusion on the completeness of the data necessary to support the existing tentative maximum residue levels (MRLs) and indications to risk managers whether or not the tentative MRLs currently established by Regulation (EC) No 396/2005 could be maintained. The statement was circulated to Member States for consultation via a written procedure before finalisation.